Portugal at the Eye of the Storm: Crisis, Austerity and the Media - Sousa, Helena; Santos, Luís António (Javnost-The Public, 2014)
The governmental change which took place in Portugal after 2011 was far more than just a new episode in the typical rotation between the two major political parties given that it occurred whilst the country was initiating a three year period of external financial control. As such the three political forces actively engaged in this rough transition have consistently pursued a stern austerity strategy imposed by creditors. This uneven platform (shaped by submission rather than by accord) has been the breeding ground for a discourse centred on the existence of a broad national consensus in support of the adopted draconian austerity measures. Irruptions of dissent have been met with contempt and have been dismissed as self-interested opinions or even as anti-patriotic. This article has four main parts. In the first one, the fundamental features of the economic and financial crisis and its consequences will be presented. In the second part, the political impacts and challenges of the crisis will be scrutinised. The political and economic impact is closely articulated with the current situation of mainstream media that is presented in the third part of the paper. As we will see in the last part of this article, a particular combination of factors in a country without financial sovereignty has created the perfect conditions for media reproduction of the government and creditors’ discourses.